2023
DOI: 10.1038/s41467-023-42657-w
|View full text |Cite
|
Sign up to set email alerts
|

ZFYVE28 mediates insulin resistance by promoting phosphorylated insulin receptor degradation via increasing late endosomes production

Liang Yu,
Mengchen Xu,
Yupeng Yan
et al.

Abstract: Insulin resistance is associated with many pathological conditions, and an in-depth understanding of the mechanisms involved is necessary to improve insulin sensitivity. Here, we show that ZFYVE28 expression is decreased in insulin-sensitive obese individuals but increased in insulin-resistant individuals. Insulin signaling inhibits ZFYVE28 expression by inhibiting NOTCH1 via the RAS/ERK pathway, whereas ZFYVE28 expression is elevated due to impaired insulin signaling in insulin resistance. While Zfyve28 overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It is well-known that brain insulin resistance plays an essential role in AD development and progression ( Sedzikowska and Szablewski, 2021 ). Regulation of Zfyve28 by Notch is well-documented ( Yu et al, 2023 ), but its plausible link to Nrf2/Bach1 (as indicated in Table 1 ) is novel. Nrf2 and Bach1 share common targets in endo/exocytosis, neurogenesis, and protein degradation pathways (such as the TET1 enzyme, ubiquitin b, and c, as shown in Table 1 ).…”
Section: Protective Pathways and Novel Therapeutic Targets Against Fe...mentioning
confidence: 99%
“…It is well-known that brain insulin resistance plays an essential role in AD development and progression ( Sedzikowska and Szablewski, 2021 ). Regulation of Zfyve28 by Notch is well-documented ( Yu et al, 2023 ), but its plausible link to Nrf2/Bach1 (as indicated in Table 1 ) is novel. Nrf2 and Bach1 share common targets in endo/exocytosis, neurogenesis, and protein degradation pathways (such as the TET1 enzyme, ubiquitin b, and c, as shown in Table 1 ).…”
Section: Protective Pathways and Novel Therapeutic Targets Against Fe...mentioning
confidence: 99%